The Influence of Perceived Ease of Use, Perceived Usefulness, and Price Value on Behavioral Intention of Telemedicine Application Users - Suwandi, Sabrina Clarissa; Chandra, Natania; Margareta, Revi; Sulaiman, Audelia Kathleen (Jurnal Sehat Indonesia (JUSINDO), 2025)
The increasing demand for healthcare services and the challenges posed by geographical barriers have made telemedicine an essential tool in providing accessible and efficient healthcare. In regions with limited access to healthcare facilities, telemedicine has proven to be a critical solution for delivering timely care and reducing the burden on traditional healthcare systems. This research aims to explore the factors influencing the behavioral intention of telemedicine application users, specifically focusing on perceived ease of use, perceived usefulness, and price value. This research employed a quantitative approach, research method with a cross-sectional approach, with data collected from 119 telemedicine users in Indonesia. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM)). The results indicate that the scores for each research variable perceived ease of use, perceived usefulness, and price value significantly and positively influence the intention to use telemedicine. The questionnaire was found to be valid and reliable, meaning that the questions in the survey are suitable for use as research instruments. These findings underscore the growing importance of telemedicine in improving healthcare accessibility and efficiency, especially in the context of post-pandemic healthcare systems.